Confrontation - Marriott, K. L.; Palmer, P. J. (Peter J.); Thompson, G. K (South Melbourne] Macmillan of Australia, 1971)
SUMMARY: Covers the origins of the earth and thedevelopment of civilised man. Describes how primitive societies use resources non-wastefully while "civilised" societies use resources much faster than they can be replaced and male unwise use of non-renewable resources
Includes bibliographies.
Intended for Year 7 Geography students
Keywords: Geography